(untitled) (Acta Polytechnica CTU Proceedings, 2020)
To enhance the safety of nuclear power, the focus of researchers all around the world has recently mainly objected on the development of Accident Tolerant Fuels. Especially the Chromium coating of current Zirconium based cladding has been widely suggested and discussed for its immense positive effect on overall cladding properties. Nevertheless, it was observed that during the first stage of the Loss of Coolant Accident, cracks appear in the Cr coating due to its inability to tolerate higher plastic strain. Therefore, experimental methodology used in this article focuses on testing fuel cladding with damaged Cr coating after the high-temperature transient. The impact of cracks on degradation of cladding mechanical properties was observed using optical microscopy, ring compression test, microhardness, and evaluating hydrogen content and weight gain.